Grouping of desi Chickpea (Cicer arietinum L.) Genotypes Based on Plant Morphological Characters - GU KULKARNI; LK SHARMA; JB PATEL (Seed Research, 2026)
An experiment was carried out at the Pulses Research Station, Junagadh Agricultural University, Junagadh, to characterize twenty five genotypes of chickpea (Cicer arietinum L.) based on plant morphological characters. Genotypes were grouped into early (9 genotypes) and medium (16 genotypes), based on time of flowering; into three classes i.e., erect (11 genotypes), semi erect (7 genotypes) and spreading (7 genotypes), based on growth habit. Based on leaflet size, genotypes were grouped into three classes of small (1 genotype), medium (12 genotypes) and large (12 genotypes), whereas, , genotypes were grouped into the classes of medium (7 genotypes) and long (18 genotypes), based on peduncle length. Based on plant height, genotypes were grouped into short (22 genotypes) and medium (3 genotypes), and based on pod size, genotypes were grouped into small (12 genotypes), medium (10 genotypes) and large (3 genotypes). Based on days to maturity, genotypes were grouped into early (17 genotypes) and medium (8 genotypes), whereas, based on the number of branches per plant, these were grouped into high (1 genotype), medium (21 genotypes) and low (3 genotypes). Number of pod per plant varied significantly among the genotypes. Number of pod per plant ranged from 78.67 (HIMCHANA 1) to 114.33 (JCP 125) with a mean of 96.24. Similarly the first pod bearing node varied significantly among the genotypes ranging from 14.67 cm (JCP 125) to 25.50 cm (HIMCHANA 1) with a mean 20.67 cm.